Analisis Kapabilitas Proses Produksi Pempek Dengan Metode Six Sigma (Pada Studi Kasus Pempek Koyek) - Kinanti Kirana Sufi; Mirza Bhilqis Jiratullah; Tuwandi Juniarto (Jurnal Teknik Ibnusina, 2026)
The rapid development of information technology presents a dual impact—both challenges and opportunities—for various business sectors, particularly Micro, Small and Medium Enterprises (MSMEs). This situation encourages MSME operators to continuously improve product quality in order to remain competitive in the market and meet increasingly high consumer expectations. This study aims to improve the pempek production process at the Pempek Koyek MSME through the application of the Six Sigma method using the DMAIC approach, which comprises the Define, Measure, Analyze, Improve, and Control stages. The data used consists of primary data obtained through direct observation of production volumes and product quality throughout the research period. In the Measure stage, Defects per Million Opportunities (DPMO) were calculated, the sigma level was determined, and process stability was evaluated using a P-Chart. Next, the Analyze stage was carried out using a Pareto chart to identify the most prevalent types of defects, as well as a cause-and-effect (fishbone) diagram to trace the main factors causing the defects. The Improve stage focused on formulating improvement proposals based on the results of the process capability analysis, taking into account human resources, raw materials, working methods, machinery, and working environment conditions. Subsequently, in the Control stage, an R-chart is applied to ensure that process variation remains within controlled limits. The research findings indicate that the implementation of the Six Sigma method can enhance the stability of the production process and maintain the consistency of the quality of the pempek produced.